Effect of Hematocrit Level on the Blood Flow through Stenosed Artery: A Theoretical Study - Malek, A.; Hoque, A.; Mohiuddin, Md. (Engineering International, 2015)
In the paper we have focused the effect of Hematocrit on flow parameters, such as resistance, frictional resistance, and skin friction due to stenosis in the artery taking blood as non-Newtonian fluid. It has been found that resistance increases with the increasing of hematocrit level and stenosis height. It is also shown that a skin-friction increase with increasing of stenosis height and decreases with the decreasing of stenosis height. Moreover the effect of stenosis shape parameter is observed on resistance and skin-friction due to different hematocrit level. Finally we compare our result graphically.
Keywords: Hematocrit; Resistance; Skin-friction; Stenosis height; Shape parameter